Stakeholder Collaboration in Sustainable Tourism: An Analysis of the Ansell and Gash Model at Sunrise Land Lombok - Baiq Dewi Kamariani; Siti Hidayatul jumaah; Hartiani Hartiani; Yuniar Affandy; Widya Hartati; Nurul Savika; Nisa Safitri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The development of the Sunrise Land Lombok tourist attraction requires collaboration among stakeholders to support sustainable tourism. However, its development still faces challenges such as suboptimal coordination between stakeholders, limited local government involvement, low private sector participation, and challenges in destination and environmental development. This study aims to analyze how stakeholder participation contributes to the success of collaboration in the development of the Sunrise Land Lombok tourist attraction. The study used a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that stakeholder participation influences the success of collaborative tourism development. The management acts as the main coordinator, the community supports through socio-economic participation, the local government plays a role in regulation, academics through research and empowerment, the media in promotion, and the private sector as a development accelerator. However, collaboration is not optimal due to limited coordination and active involvement of several stakeholders, especially the local government and the private sector. This study concludes that increasing stakeholder participation, coordination, and synergy are important factors in realizing sustainable tourism development in Sunrise Land Lombok.